CREATING INCLUSIVE LANGUAGE LEARNING ENVIRONMENTS: ADDRESSING THE NEEDS OF DIVERSE LEARNERS - Aswad, Muhammad; Wirentake, Wirentake (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
In today's diverse educational landscape, there is a growing need to create inclusive language learning environments that cater to the diverse needs of learners. This requires an understanding of various instructional design frameworks and practices that promote inclusivity, such as differentiated instruction and Universal Design for Learning, which can significantly enhance engagement and support for all students, particularly those from culturally and linguistically diverse backgrounds. To achieve this, educators must implement strategies that recognize and celebrate diversity, fostering a learning atmosphere where all students feel valued and capable of succeeding, thereby enhancing overall learning outcomes and experiences for everyone involved. The purpose of this research is to explore strategies for creating inclusive language learning environments that address the diverse needs of learners. This study employed a qualitative research approach, conducting a comprehensive review of relevant literature to identify and analyze the key factors and strategies for creating inclusive language learning environments.